2003
DOI: 10.1007/s00232-003-2027-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol Phosphate Kinases Put PI4,5P 2 in Its Place

Abstract: Phosphatidylinositol 4,5 bisphosphate (PI4,5P(2)) is a critical second messenger that regulates a myriad of diverse cellular activities including modulation of the actin cytoskeleton, vesicle trafficking, focal adhesion formation, and nuclear events. In order to effectively regulate these disparate cellular events, synthesis of PI4,5P(2) by phosphatidylinositol phosphate kinases (PIP kinases) must be both spatially and temporally regulated. Two subfamilies of PIP kinases, types I and II, allow the generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
264
0
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(283 citation statements)
references
References 84 publications
5
264
0
14
Order By: Relevance
“…Membrane phospholipids can directly influence the function of many channels, including HCN1, 2 and 4 (Pian et al, 2007;Suh and Hille, 2008); therefore, we first investigated whether endogenous PIP 2 modulated HCN channel gating in IGL neurons. At micromolar concentrations, wortmannin blocks type III phosphatidylinositol 4-kinase (PI4K III) (Nakanishi et al, 1995), thereby inhibiting the final step in the biosynthetic pathway for PIP 2 (Doughman et al, 2003;Balla and Balla, 2006;Sasaki et al, 2009). Brain slices were preincubated at 30Ā°C in ACSF containing 15 M wortmannin or 0.1% DMSO (the vehicle as control) for Ļ³45 min before recording.…”
Section: Depletion Of Endogenous Pip 2 Pools Inhibits Hcn3 Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane phospholipids can directly influence the function of many channels, including HCN1, 2 and 4 (Pian et al, 2007;Suh and Hille, 2008); therefore, we first investigated whether endogenous PIP 2 modulated HCN channel gating in IGL neurons. At micromolar concentrations, wortmannin blocks type III phosphatidylinositol 4-kinase (PI4K III) (Nakanishi et al, 1995), thereby inhibiting the final step in the biosynthetic pathway for PIP 2 (Doughman et al, 2003;Balla and Balla, 2006;Sasaki et al, 2009). Brain slices were preincubated at 30Ā°C in ACSF containing 15 M wortmannin or 0.1% DMSO (the vehicle as control) for Ļ³45 min before recording.…”
Section: Depletion Of Endogenous Pip 2 Pools Inhibits Hcn3 Functionmentioning
confidence: 99%
“…Among the ligands that can influence HCN gating, the best understood is cAMP; however, the regulation of cellular physiology by I h in IGL neurons is not mediated by this nucleotide. PIP 2 is also an important modulator that regulates various cellular activities including ion channel function (Doughman et al, 2003;Suh and Hille, 2008). Incubation with wortmannin, which leads to depletion of endogenous PIP 2 pools, resulted in a marked hyperpolarizing shift in voltage-dependent activation of both native and recombinant HCN3 channels (Fig.…”
Section: Pip 2 Is Crucial For Gating Of Hcn3 Channelsmentioning
confidence: 99%
“…Three major PI5KI isoforms (ā£, ā¤, and ā„) have been identified. [12][13][14][15] Increasing evidences indicate that PI5KIs, providing spatially and functionally distinct PIP2 pools, guarantee the regulation of specific cellular events: PI5KIā„, for instance, is required for focal adhesion and synaptic vesicle trafficking, 16,17 PI5KIā¤ for constitutive receptor endocytosis, 18 whereas PI5KIā£ acts in the regulation of processes dependent on local changes of actin dynamics, such as membrane ruffling and phagocytosis. 19,20 In this report, we took advantage of the fusion protein consisting of GFP and the pleckstrin homology (PH) domain of PLCā¦1, that is known to bind PIP2 with high affinity and specificity, [21][22][23] to monitor the dynamics and function of PIP2 during the cytotoxic event.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism by which PtdIns(4,5)P 2 is generated is through type I phosphatidylinositol phosphate kinases (PIPKI), which produce PtdIns(4,5)P 2 through the phosphorylation of the fifth hydroxyl of phosphatidylinositol (4)-phosphate (PI4P) (Doughman et al, 2003). The PIPKI family includes three isoforms: ā£, ā¤, and ā„.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PIPKIā„ mRNA is alternatively spliced to form PIPKIā„635 and PIPKIā„661, which differ by a 26-amino acid C-terminal extension. Previous work has shown that the PIPKI family of lipid kinases display distinct subcellular distributions in fibroblasts (Di Paolo et al, 2002;Ling et al, 2002;Doughman et al, 2003). PIPKIā£ targets to the leading edge of cells where it regulates membrane ruffling (Doughman et al, 2003), whereas PIPKIā„661 targets to focal adhesions and may regulate integrin-mediated adhesions during cell migration via an interaction with the cytoskeletal protein talin (Di Paolo et al, 2002;Ling et al, 2002).…”
Section: Introductionmentioning
confidence: 99%